Conservation of cultural heritage : key principles and approaches - Szczepanowska, Hanna M. (Routledge, 2013)
"Conservation of Cultural Heritage covers the methods and practices needed for future museum professionals who will be working in various capacities with museum collections and artefacts. It also assists current professionals in understanding the complex decision making processes that faces conservators on a daily basis. Covering a broad range of topics that are key to sound conservation in the museum, this volume is an important tool for students and professional alike in ensuring that best practice is followed in the preservation of important collections"--